2012
DOI: 10.1097/mpa.0b013e31824bde37
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Administration Impairs Pancreatic Repair After Injury

Abstract: Objectives Alcohol abuse is one of the most common factors associated with acute and chronic pancreatitis. Although it is evident that alcohol abuse can have an important role in the development of pancreatitis, it does not appear that alcohol abuse alone is responsible for this disease. We investigated the involvement of ethanol in impairment of pancreatic repair after induction of pancreatitis. Methods A biologically relevant mouse model of alcoholic pancreatitis, combining chronic ethanol consumption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…Based on clinical observations in human beings, it is believed that in cases of acute pancreatitis, which resolve, the pancreas regenerates to its full structural and functional capacity after an acute episode. This concept is supported by many studies in experimental animals, which have demonstrated structural and functional repair of the pancreas after experimentally induced pancreatitis [1][2][3][4][5] . In cases of severe acute pancreatitis systemic inflammation develops and can lead to multiorgan failure and death.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Based on clinical observations in human beings, it is believed that in cases of acute pancreatitis, which resolve, the pancreas regenerates to its full structural and functional capacity after an acute episode. This concept is supported by many studies in experimental animals, which have demonstrated structural and functional repair of the pancreas after experimentally induced pancreatitis [1][2][3][4][5] . In cases of severe acute pancreatitis systemic inflammation develops and can lead to multiorgan failure and death.…”
Section: Introductionmentioning
confidence: 55%
“…These findings have lead to the suggestion that these cytokines and growth factors act on pancreatic stellate cells in an autocrine manner, thereby perpetuating their activation [16] . This autocrine loop may help to explain both the apparent inability of the pancreas to fully recover from injury in the continued presence of ethanol, and the extremely common association between alcohol abuse and chronic pancreatitis [3,14] . Although it is well established that pancreatic stellate cells are primarily responsible for the deposition and degradation of components of the extracellular matrix, acinar cells can also contribute to the deposition of extracellular matrix components.…”
Section: Involvement Of Pancreatic Stellate Cells In Alcoholic Pancrementioning
confidence: 99%
See 1 more Smart Citation
“…In experimentally infected mice, the viral titers in the spleen peak 2-4 days post infection (PI) (30). Because of the highly vascular nature of the spleen, the titer in the spleen presumably represents the titer in the blood (level of viremia) of infected animals.…”
Section: Viral Infection and Generation Of Pancreatitismentioning
confidence: 99%
“…Although typically associated with heart disease, these viruses have been isolated from the pancreata of patients with pancreatitis (11,26,46). Furthermore, coxsackieviruses have been shown to replicate to high titers in the pancreas and cause extensive pancreatic tissue damage in experimental animal models (30,34). In fact, in mice, if these viruses do not replicate to high titer in the pancreas, they do not cause heart disease (13,34).…”
Section: Introductionmentioning
confidence: 99%